2021
DOI: 10.1111/jfpp.15289
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet/visible intense pulsed light irradiation of fresh‐cut avocado enhances its phytochemicals content and preserves quality attributes

Abstract: Avocado fruits are hardly commercialized as a fresh-cut product due to its high perishability and the accelerated loss of its quality attributes (such as color and texture) during storage. Enzymatic browning and softening are two of the main quality problems perceived by consumers in avocado. Previous research works proposed the use of dipping treatments to effectively preserve the color and texture of fresh-cut avocados (Ramos-Villarroel et al., 2011). However, as freshcut avocados using dipping treatments st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
1
5
0
1
Order By: Relevance
“…This trend was especially evident in tomatoes subjected to PL treatments with broad‐spectrum light (180–1100 nm), which exhibited a 33.4% decrease in chlorophyll concentration at day 1 in comparison to untreated tomatoes. Similar results have been reported in PL‐treated fresh‐cut avocado after applying the same wavelength ranges (Velderrain‐Rodríguez et al., 2021 ). Authors attributed this reduction to photooxidative reactions, the loss of cellular compartmentalization, and the action of chlorophyllase, chlorophyll oxidase, and POD.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This trend was especially evident in tomatoes subjected to PL treatments with broad‐spectrum light (180–1100 nm), which exhibited a 33.4% decrease in chlorophyll concentration at day 1 in comparison to untreated tomatoes. Similar results have been reported in PL‐treated fresh‐cut avocado after applying the same wavelength ranges (Velderrain‐Rodríguez et al., 2021 ). Authors attributed this reduction to photooxidative reactions, the loss of cellular compartmentalization, and the action of chlorophyllase, chlorophyll oxidase, and POD.…”
Section: Resultssupporting
confidence: 87%
“…In this regard, the fast accumulation of carotenoids in tomatoes after the application of PL treatments was likely related to the modulation of phytoene synthase (PSY) activity, considered the main enzyme in carotenoids biosynthesis, triggered by the high ratio of red and far‐red light. Previous studies have reported similar carotenoid increment during post‐treatment time of different PL‐treated fruits, such as tomato (200–1100 nm; 1, 2, 4 J cm –2 ) (Pataro et al., 2015 ), fresh‐cut avocado (400–1100 nm; 12 J cm –2 ) (Velderrain‐Rodríguez et al., 2021 ), and mango (200–1100 nm; 1.2 J cm –2 ) (Lopes et al., 2016 ). However, carotenoids reduction has also been reported in other vegetable products such as bell pepper (190–1100 nm; 4–8 J cm –2 ) (Rybak et al., 2021 ).…”
Section: Resultsmentioning
confidence: 68%
“…On the contrary, the L *, a *, and b * values for UV‐C‐treated fresh‐cut watermelon show no alteration ( p > 0.05) (Artés‐Hernández et al, 2021). Velderrain‐Rodríguez et al (2021) and Ramos‐Villarroel et al (2011) also reported color stability in freshly cut avocados exposed to PL treatment.…”
Section: Resultsmentioning
confidence: 91%
“…The release of phenolic compounds bound to cell wall polysaccharides and the depolymerization of phenolic polymers such as tannins [Xiang et al, 2020] might have occurred. On the other hand, phenolics can be used as substrates for enzymes such as β-glucosidase, PPO, and POD [Velderrain-Rodríguez et al, 2021]. These processes may occur to varying degrees in mango samples subjected to various treatments and thus result in different total phenolic content.…”
Section: Resultsmentioning
confidence: 99%